2021
DOI: 10.1007/s10811-021-02515-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of monocultures and a mixed culture of three Chlorellaceae strains to optimize biomass production and biochemical content in microalgae grown in a greenhouse

Abstract: Light and temperature are important environmental conditions affecting microalgal growth in outdoor culture. It is essential to evaluate microalgae strains growing under outdoor conditions where they are subjected to variable environmental parameters. The present study investigated three Chlorellaceae strains (Micractinium sp. MACC-728, Chlorella sorokiniana MACC-438, and C. sorokiniana MACC-452) and a mixed culture combining these three strains. Cultures were grown in 2-L bioreactors in a greenhouse over 3 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…These naturally produced compounds are a variety of biologically active molecules that can positively affect plant growth as well as the efficiency of nutrient use and increase plant tolerance to abiotic stresses. In this respect, microalgae strains showing biostimulating features have been studied as these microorganisms can be produced in controlled mass cultures and their metabolic plasticity provides the possibility to modulate biomass composition which is one of the critical aspects in the production of biostimulants [ 57 , 58 , 59 , 60 , 61 , 62 ]. Recently, the pilot production trial of Scenedesmus and Chlorella biomass with biostimulating features was realized using brewery [ 63 ] or municipal WW [ 37 , 64 ] as sources of nutrients which significantly reduced the costs of biomass production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These naturally produced compounds are a variety of biologically active molecules that can positively affect plant growth as well as the efficiency of nutrient use and increase plant tolerance to abiotic stresses. In this respect, microalgae strains showing biostimulating features have been studied as these microorganisms can be produced in controlled mass cultures and their metabolic plasticity provides the possibility to modulate biomass composition which is one of the critical aspects in the production of biostimulants [ 57 , 58 , 59 , 60 , 61 , 62 ]. Recently, the pilot production trial of Scenedesmus and Chlorella biomass with biostimulating features was realized using brewery [ 63 ] or municipal WW [ 37 , 64 ] as sources of nutrients which significantly reduced the costs of biomass production.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the pilot production trial of Scenedesmus and Chlorella biomass with biostimulating features was realized using brewery [ 63 ] or municipal WW [ 37 , 64 ] as sources of nutrients which significantly reduced the costs of biomass production. Biotests also showed that Micractinium is a valuable strain with biostimulating activity for agricultural use based on its auxin-like activity [ 61 ]. Downstream processes, e.g., dissolved air flotation, centrifugation, sonication, and enzymatic hydrolysis, are being optimized to prepare biomass extracts in DEMO scale for field or greenhouse hydroponic application.…”
Section: Discussionmentioning
confidence: 99%
“…The plant biostimulating activity of the extracts was measured using the mung bean (Vigna radiata) rooting bioassay [44,45]. The beans were germinated in moist vermiculite at 26°C in a 16:8 h light:dark photoperiod and 120 µmol photons m − 2 s − 1 light intensity.…”
Section: Mung Bean Rooting Test (Auxin-like Activity)mentioning
confidence: 99%